Embedding Local Wisdom Values in the Pedagogical Profession Course to Enhance Students’ Professional Identity - Nana Erna; Nurfajriah Basri; Nurianti HS; Pebrina Nurwahyuningsih; Titin Suhartini; Eka Fatmawati Hading (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
This study investigates how local wisdom values such as sipakatau (humanity), sipakalebbi (respect), and sipakainge (moral reminder) are integrated into the Pedagogical Profession course and how this integration contributes to the development of pre-service teachers’ professional identity. The purpose of this research is to examine the extent to which culturally grounded pedagogical practices shape students’ ethical awareness, character formation, and professional self-concept. Using a qualitative case study design, data were collected from 20 English Education undergraduates through classroom observations, document analysis, and semi-structured interviews. Local wisdom values were embedded through structured reflective journals, culturally oriented case analyses, and project-based learning tasks. Thematic analysis generated three key themes: (1) Contribution to Professional Identity, (2) Affective and Character Formation, and (3) Professional Identity Internalization. Findings show that engaging with local wisdom strengthened students’ ethical reasoning, emotional sensitivity, and reflective capacity. Students also reported increased commitment to professional responsibilities and deeper alignment with cultural and moral principles. The study concludes that integrating local wisdom into teacher education supports both professional competence and value internalization, offering important implications for culturally responsive curriculum design, teacher preparation programs, and moral development in higher education.